Effectiveness and Challenges of Implementing Augmented Reality (AR) Technology in Science Learning in Elementary Schools: A Literature Study - Early Regina Destyani; Bambang Subali; Nuni Widiarti (FKIP - Universitas Riau, 2026)
In the era of digital technology advancement, education is also evolving rapidly. This provides a great opportunity for teachers to improve the quality of the teaching and learning process, especially in teaching media. One of the emerging technologies is augmented reality (AR) which combines the real world with digital elements to provide a more interactive and visual learning experience. This article aims to explore the effectiveness of using AR in learning science in elementary schools, especially in improving the understanding of abstract concepts that are difficult to understand. Through a literature review of previous studies, this article highlights the benefits of AR such as increased student understanding, learning engagement, and motivation. However, challenges such as limited infrastructure, high costs, and teacher readiness still hinder its implementation. This study concludes that AR has great potential to transform science learning, although it requires appropriate implementation strategies, including adequate infrastructure, teacher training, and relevant content development. Based on the literature review, the development of curriculum-appropriate AR applications and their long-term implementation is still not widely explored and can be the focus of future studies.